Pengaruh Struktur Modal Dan Ukuran Perusahaan Terhadap Return On Asset (ROA) Pada PT. Hutama Karya (Persero) - Dahnia Suryana; Aliah Pratiwi; Wulandari Wulandari (Sharing: Journal of Islamic Economics Management and Business, 2024)
This research aims to determine the influence of capital structure and company size on return on assets (ROA) at PT. Hutama Karya (Persero). This type of research is associative. The research instrument uses a Likert scale questionnaire. The research instrument used is a list of tables containing data on total debt, total equity, total assets and net profit at PT. Hutama Karya (Persero) for 10 years, namely from 2014 to 2023. The population in this research is all financial reports of PT. Hutama Karya (Persero) has been listed on the IDX from 2013 to 2023, which is 11 years. The sample in this research is the financial report of PT. Hutama Karya (Persero) for 10 years, namely from 2014 to 2023. The sampling technique used in this research was purposive sampling. Data collection techniques in this research are documentation and literature study. The data analysis technique uses the classical assumption test, multiple linear regression, multiple correlation coefficient, determination test, t test and f test. The research results show that Debt to Equity Ratio (DER) and Company Size influence Return On Assets (ROA) at PT. Hutama Karya (Persero).